Design and Development of Coffee Machine Control System Using Fuzzy Logic - Hadianto, Eko; Amanda, Djaja; Hindarto, Djarot; Makmur, Amelia; Santoso, Handri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The food and beverage industry is currently rife in urban and outside cities. Many locations are used as places to sell drinks, especially coffee which is a native plant of Indonesia. Nowadays, coffee compounding requires good technology. There are many coffee processing machines on the market. The coffee machine is capable of making expresso coffee, latte coffee and others. This coffee machine also combines coffee ingredients, sugar and milk as a carrier for a delicious aroma. In addition, the water pressure from the coffee machine heating boiler, the strong pressure of the coffee machine piston also affects the results of making a cup of coffee, the stronger the pressure, the thicker the coffee produced and the slower the flow of water in the coffee machine. glass of water because basically the stronger the pressure applied to it. the coffee grounds, the tighter and tighter the gaps that the water itself will pass, as well as the thickness of the resulting coffee water will be more concentrated. With Fuzzy Inference, it is possible to determine the optimal pressure to be exerted by the coffee machine piston based on the weight of the coffee grounds (grams) on the coffee machine piston and the specifications of the type of coffee machine used. Determining the optimal pressure on the coffee grounds will affect the taste of the coffee water produced and the speed of making a cup of coffee. This study uses the optimal pressure on the piston using the fuzzy inference method. The purpose of this research is to create a simulation for evaluating the performance of a coffee machine using fuzzy logic to solve the problem of damage to the piston. The fuzzy approach in this research uses the fuzzy Takagi Sugeno Kang method.